Tribological characteristics of Al–Mg–Si–Cu alloy against die steel under elevated temperatures in simulated hot extrusion environment - Zhiwen Liu; Ming Zhang; Ping Yan; Xiao Liu; Luoxing Li (Journal of Materials Research and Technology)
Friction is a considerable boundary condition in aluminum alloy hot extrusion. In this study, ball-on-disc friction tests at temperatures of 25–500 °C were performed to equivalently simulate the interface tribological behaviors between Al–Mg–Si–Cu alloy and die steel in hot extrusion. The wear tracks and wear debris on disc samples were observed by means of ultradepth 3D microscopy, field-emission scanning microscope and energy dispersive spectroscopy. The change trends of wear depth, width and wear rate of aluminium disc with temperature and wear cycles were investigated. The evolutions of wear mechanism and friction coefficient with temperature were revealed. A mechanical analytical model for identifying adhesion and ploughing friction components during friction was established. The results show that as temperature rises, wear rate of aluminum disc increases gradually, while the average friction coefficient increases first rapidly and then decreases, which is associated with the changes of friction and wear mechanisms. The adhesion friction force constitutes the majority of total friction force, while ploughing friction force accounts for less than 3 %. Compared with the large variation of adhesion friction coefficient during friction, shear friction stress can tend to be stable and is not affected by the change of contact area, which may can better characterize the adhesion frictional behavior of die interface in aluminum alloy hot extrusion. The quantitative relationship between temperature and steady shear friction stress was described by an inverse polynomial peak function.